Isothermal annealing process of amorphous alloy
Through a specific isothermal annealing process, the amorphous alloy material is processed, and the problem of crystallization transformation at high temperature or high pressure is solved, its plasticity and strength are improved, and glass formation ability and thermal stability are enhanced.
Patent Information
- Application Number
- CN202410611468.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2025-02-11
AI Technical Summary
Amorphous alloys are prone to crystallization and transformation under high temperature or high pressure, resulting in a sharp decline in their excellent performance. It is difficult for existing isothermal annealing processes to effectively improve their plasticity and strength.
An isothermal annealing process is adopted, including mixing high-purity sponge zirconium, copper, pure aluminum and silver in a specific proportion, preparing alloy round rods by arc smelting vacuum casting method, and then heating to 980°C in a trolley- 1000℃, then naturally drop to 750℃, keep the heat at 5h-7h, then gradually cool down to 450℃, and finally air-cooling naturally.
The amorphous alloy material treated by this process has good glass formation ability and thermal stability, and its plasticity and strength have also been effectively improved.
Smart Images

Figure CN119411041A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of isothermal annealing of amorphous alloys, in particular to an isothermal annealing process of an amorphous alloy. Background Art
[0002] Compared with crystalline materials, amorphous alloys have unique microstructures. Their atoms are no longer arranged in a periodic long-range order, and there are no crystal defects such as grain boundaries and dislocations in crystalline alloy materials. They have always attracted extensive attention from researchers. This structure gives them unique physical and chemical properties, such as high strength, high hardness, high wear resistance, low elastic modulus and strong corrosion resistance, and makes them have good application prospects in military equipment, aerospace, marine engineering, medicine and biology, electronic information and other fields. However, amorphous alloys are metastable materials. Under high temperature or high pressure, they will undergo a crystallization transition to a thermodynamic equilibrium state, causing some of their excellent properties to drop sharply. Therefore, stability, plastic deformation ability and fracture behavior research have always been one of the focuses in the field of amorphous alloys.
[0003] Isothermal annealing, as an effective means to improve material properties, has been applied to amorphous alloys by scholars at home and abroad and has achieved many successes. Currently, there is an urgent need for an isothermal annealing process for amorphous alloys to improve the plasticity and strength of amorphous alloys. Summary of the invention
[0004] To achieve the above objectives, the present invention is implemented by the following technical solutions: an isothermal annealing process for an amorphous alloy, characterized in that it comprises the following steps: S1, take 45-50 parts of high-purity sponge zirconium, 45-50 parts of copper, 7-10 parts of pure aluminum and 3-5 parts of silver as raw materials, put them into a mixing device and mix them evenly; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round bar in step S2 into a trolley-type heat treatment furnace, and gradually heating the alloy round bar to between 980°C and 1000°C; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 5h-7h; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
[0005] Preferably, 45 parts of the high-purity sponge zirconium, 45 parts of the copper, 7 parts of the pure aluminum, and 3 parts of the silver are taken, and the accurately weighed metal elements are cleaned by ultrasonic vibration.
[0006] Preferably, the purity of the high-purity sponge zirconium is 99.9%, the purity of the copper is 99.8%, the purity of the pure aluminum is 99.9%, and the purity of the silver is 99.99%.
[0007] Preferably, the heating rate of the alloy round rod in step S2 is less than 200° C. / hour.
[0008] Preferably, in step S5, the temperature inside the heat treatment furnace decreases at a rate of 50° C. / hour.
[0009] The present invention provides an isothermal annealing process for an amorphous alloy, which has the following beneficial effects: The isothermal annealing process of the amorphous alloy, the alloy material after the isothermal annealing process has good glass forming ability and thermal stability, and its plasticity and strength are also effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The XRD spectrum of the amorphous alloy of the present invention; Figure 2 The DSC curve of the amorphous alloy of the present invention is as follows; Figure 3 is the XRD spectrum of the amorphous alloy after isothermal annealing of the present invention; Figure 4 TEM image and selected area electron diffraction pattern image of the amorphous alloy after isothermal annealing of the present invention; Figure 5 The uniaxial compression stress-strain curves of the amorphous alloy after casting and isothermal annealing of the present invention; Figure 6 The room temperature compression fracture morphology of the amorphous alloy after casting and isothermal annealing of the present invention; Figure 7 These are SEM images of the side surfaces of the samples of the present invention after being cast, isothermally annealed at 741K, 746K, 751K and 756K. DETAILED DESCRIPTION
[0011] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0012] In the first embodiment, the present invention provides a technical solution: an isothermal annealing process for an amorphous alloy, comprising the following steps: S1. Take 45 parts of high-purity sponge zirconium, 45 parts of copper, 7 parts of pure aluminum and 3 parts of silver as raw materials, and use ultrasonic vibration to clean the accurately weighed metal elements, and then put them into a mixing device to mix them evenly. The purity of high-purity sponge zirconium is 99.9%, the purity of copper is 99.8%, the purity of pure aluminum is 99.9%, and the purity of silver is 99.99%; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round rod in step S2 into a trolley-type heat treatment furnace, gradually heating the alloy round rod to 980° C., and the heating rate of the alloy round rod is less than 200° C. / hour; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 5 hours; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C, and the speed of the temperature drop inside the heat treatment furnace is 50°C / hour; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
[0013] In the second embodiment, the present invention provides a technical solution comprising the following steps: S1. Take 48 parts of high-purity sponge zirconium, 48 parts of copper, 8 parts of pure aluminum and 4 parts of silver as raw materials, and use ultrasonic vibration to clean the accurately weighed metal elements, and then put them into a mixing device to mix them evenly. The purity of high-purity sponge zirconium is 99.9%, the purity of copper is 99.8%, the purity of pure aluminum is 99.9%, and the purity of silver is 99.99%; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round rod in step S2 into a trolley-type heat treatment furnace, gradually heating the alloy round rod to 990° C., and the heating rate of the alloy round rod is less than 200° C. / hour; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 6 hours; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C, and the speed of the temperature drop inside the heat treatment furnace is 50°C / hour; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
[0014] In a third embodiment, the present invention provides a technical solution comprising the following steps: S1. Take 50 parts of high-purity sponge zirconium, 50 parts of copper, 10 parts of pure aluminum and 5 parts of silver as raw materials, and use ultrasonic vibration to clean the accurately weighed metal elements, and then put them into a mixing device to mix them evenly. The purity of high-purity sponge zirconium is 99.9%, the purity of copper is 99.8%, the purity of pure aluminum is 99.9%, and the purity of silver is 99.99%; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round rod in step S2 into a trolley-type heat treatment furnace, gradually heating the alloy round rod to 1000° C., with the heating rate of the alloy round rod being less than 200° C. / hour; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 7 hours; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C, and the speed of the temperature drop inside the heat treatment furnace is 50°C / hour; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
[0015] In a fourth embodiment, the present invention provides a technical solution comprising the following steps: S1. Take 45 parts of high-purity sponge zirconium, 50 parts of copper, 7 parts of pure aluminum and 5 parts of silver as raw materials, and use ultrasonic vibration to clean the accurately weighed metal elements, and then put them into a mixing device to mix them evenly. The purity of high-purity sponge zirconium is 99.9%, the purity of copper is 99.8%, the purity of pure aluminum is 99.9%, and the purity of silver is 99.99%; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round rod in step S2 into a trolley-type heat treatment furnace, gradually heating the alloy round rod to 980° C., and the heating rate of the alloy round rod is less than 200° C. / hour; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 7 hours; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C, and the speed of the temperature drop inside the heat treatment furnace is 50°C / hour; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
[0016] In a fifth embodiment, the present invention provides a technical solution comprising the following steps: S1. Take 50 parts of high-purity sponge zirconium, 45 parts of copper, 10 parts of pure aluminum and 3 parts of silver as raw materials, and use ultrasonic vibration to clean the accurately weighed metal elements, and then put them into a mixing device to mix them evenly. The purity of high-purity sponge zirconium is 99.9%, the purity of copper is 99.8%, the purity of pure aluminum is 99.9%, and the purity of silver is 99.99%; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round rod in step S2 into a trolley-type heat treatment furnace, gradually heating the alloy round rod to 1000° C., with the heating rate of the alloy round rod being less than 200° C. / hour; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 5 hours; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C, and the speed of the temperature drop inside the heat treatment furnace is 50°C / hour; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
[0017] In a sixth embodiment, the present invention provides a technical solution comprising the following steps: S1. Take 45 parts of high-purity sponge zirconium, 45 parts of copper, 10 parts of pure aluminum and 5 parts of silver as raw materials, and use ultrasonic vibration to clean the accurately weighed metal elements, and then put them into a mixing device to mix them evenly. The purity of high-purity sponge zirconium is 99.9%, the purity of copper is 99.8%, the purity of pure aluminum is 99.9%, and the purity of silver is 99.99%; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round rod in step S2 into a trolley-type heat treatment furnace, gradually heating the alloy round rod to 980° C., and the heating rate of the alloy round rod is less than 200° C. / hour; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 5 hours; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C, and the speed of the temperature drop inside the heat treatment furnace is 50°C / hour; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
[0018] In a seventh embodiment, the present invention provides a technical solution comprising the following steps: S1. Take 50 parts of high-purity sponge zirconium, 50 parts of copper, 7 parts of pure aluminum and 3 parts of silver as raw materials, and use ultrasonic vibration to clean the accurately weighed metal elements, and then put them into a mixing device to mix them evenly. The purity of high-purity sponge zirconium is 99.9%, the purity of copper is 99.8%, the purity of pure aluminum is 99.9%, and the purity of silver is 99.99%; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round rod in step S2 into a trolley-type heat treatment furnace, gradually heating the alloy round rod to 1000° C., with the heating rate of the alloy round rod being less than 200° C. / hour; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 7 hours; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C, and the speed of the temperature drop inside the heat treatment furnace is 50°C / hour; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
[0019] The microstructure and fracture morphology of the alloy samples were analyzed by using D / Max-2200 XRD, Tecnai G220 TEM and Quanta2000 environmental scanning electron microscope (SEM); the room temperature uniaxial compression mechanical property test was carried out on an INSTRON-5569 testing machine. Since the alloy samples treated in the first embodiment have better properties, the following are the results and analysis of the alloy samples in the first embodiment; XRD was used to identify the phase structure of the alloy. Usually, the diffraction curve of a single-phase amorphous alloy showed diffuse diffraction peaks, while that of an amorphous composite material showed a superposition of sharp diffraction peaks with different intensities and diffuse diffraction peaks. XRD detection was carried out on a D / Max-2200 XRD, which used a Cu Kα ray source, a wavelength of λ=1.540598Å, a scanning angle of 20°-80°, and a scanning speed of 0.05° / s. The compression performance of the alloy sample was tested by uniaxial compression test using INSTRON-5569 testing machine. The diameter of the compression specimen was 4 mm, the compression surface was polished with 1000# sandpaper, the radial length was 8 mm, and it was perpendicular to the compression surface. The compression rate was 0.2 mm / min.
[0020] Figure 1 This is the XRD spectrum of Cu45Zr45Ag7Al3 amorphous alloy. It can be seen from the figure that the alloy sample has only one diffuse peak near 40°, which is a typical structural feature of amorphous alloys. Figure 1Figure b is the TEM image of the alloy sample and its selected area electron diffraction pattern. As shown in the figure, there is no obvious ordered atomic arrangement in the TEM and no obvious crystalline phase. The corresponding selected area electron diffraction is a typical amorphous diffraction ring, showing typical amorphous structural characteristics, further indicating that the cast Cu45Zr45Ag7Al3 amorphous alloy is completely composed of an amorphous structure.
[0021] The DSC curve of Cu45Zr45Ag7Al3 amorphous alloy was measured at a heating rate of 10K / min. Figure 2 As shown in the figure, it can be seen that the amorphous alloy has only one obvious endothermic reaction and crystallization exothermic peak, and there is a wide supercooled liquid phase region between the two. The tangent method can be used to calibrate the alloy sample's glass transition temperature Tg, crystallization initial temperature Tx and crystallization peak temperature Tp to be 711.8K, 772.8K and 774.9K, respectively. The supercooled liquid phase region ΔTx (ΔTx=Tx-Tg) can be calculated to be 61K, indicating that the alloy has good glass forming ability and thermal stability. According to the above experimental results, 741K, 746K, 751K, and 756K are selected within the supercooled liquid phase region ΔTx as the isothermal annealing target temperatures.
[0022] Figure 3 Figure 2 is the XRD spectrum of the sample after isothermal annealing. After annealing at 741K and 746K, the alloy sample is an amorphous structure as a whole, but the curve has a sharpening trend near 40°; after annealing at 751K and 756K, the diffuse peaks of the XRD spectrum of the amorphous alloy sample gradually disappear, and the degree of sharpening is more obvious than that of the sample after annealing at 741K and 746K. It is calibrated as Cu10Zr7, Cu8Zr3 and AlCu2Zr phases, indicating that the crystallization phenomenon of the amorphous alloy becomes more serious with the increase of the isothermal temperature. At this time, the alloy sample is an amorphous-crystal composite material.
[0023] TEM image and selected area electron diffraction pattern of the amorphous alloy sample after isothermal annealing are as follows: Figure 4 As shown. Figure 4 It can be clearly seen from a and b in that although the XRD spectrum results show that the amorphous alloy sample still has an amorphous structure as a whole after isothermal annealing at 741K and 746K, many nanoscale particles (5 nm -20nm) are dispersed in the amorphous matrix, and the particles gradually grow as the temperature rises. Electron diffraction spot calibration shows that the nano-precipitated phase is Cu10Zr7 phase; after isothermal annealing at 751K, part of the Cu10Zr7 particle phase is transformed into a cellular structure, such as Figure 4 As shown in Figure c, this cellular structure is similar to grains, but there is no obvious boundary between the cells. After calibration, it can be known that this cellular structure is AlCu2Zr; when the annealing temperature reaches 756K, the alloy crystallization phenomenon is more obvious, and the main precipitated phase is AlCu2Zr, followed by Cu8Zr3 phase and Cu10Zr7 phase.
[0024] The precipitated phase during isothermal annealing of amorphous alloys is mainly controlled by atomic diffusion and the interface energy between the precipitated phase and the matrix. The closer the precipitated phase structure is to the amorphous structure, the lower the interface energy is, and the easier the crystallization nucleation is. At the same time, the atomic ratio of the Cu10Zr7 phase is similar to the atomic ratio of Cu and Zr in the matrix, and the structure is close to the amorphous state. Therefore, nucleation does not require atomic diffusion and can precipitate at a lower annealing temperature. The nucleation of the AlCu2Zr phase requires the diffusion of Al atoms and the expulsion of Zr atoms, both of which require sufficient energy. As the annealing temperature gradually increases, higher energy is provided, and the diffusion of Al and Zr atoms becomes more intense, which is conducive to the nucleation of the AlCu2Zr phase. However, the formation of the AlCu2Zr phase will lead to the formation of Al-poor and Zr-rich regions, increasing the concentration of Zr and Cu near the region, further promoting the formation of Cu10Zr7 and Cu8Zr3.
[0025] Figure 5 Figure a is the uniaxial compression stress-strain curve of the sample after casting and isothermal annealing at room temperature (strain rate is 5×10-4s-1). According to the curve, except for the no obvious plastic deformation characteristics after isothermal annealing at 756K, the casting, 741K, 746K and 751K isothermal annealing all have certain plastic strain characteristics. Figure 5 b is the comparison curve of fracture strength and plastic strain of the samples after casting and isothermal annealing. Figure 4 It can be seen that after isothermal annealing, the fracture strength and plastic strain of the amorphous alloy samples generally increase first and then decrease, among which the fracture strength reaches the maximum value (1748MPa) at 746K, and the plastic strain reaches the maximum value (0.68%) at 741K.
[0026] Figure 6 The room temperature compression fracture morphology of the samples after casting and isothermal annealing. Figure 6 As can be seen in a, b and c, the fracture surfaces of the cast, 741K and 746K isothermal annealed samples are mainly composed of crescent-shaped veins and molten droplets. This is due to the release of elastic potential energy during deformation of the amorphous alloy, which leads to a rapid increase in temperature near the main shear band. In addition, the veins of the samples after isothermal annealing at 746K are finer than those at 741K. Figure 5 From the stress-strain curve, it can be seen that the existence of nano-precipitated phase effectively hinders the uniform rheological deformation of the alloy. After isothermal annealing at 751K, herringbone-shaped and vein-shaped lines and a large number of slip areas exist in the fracture. After isothermal annealing at 756K, the vein-shaped lines on the fracture completely disappear, and the fracture is mainly replaced by intergranular fracture characteristics, indicating that the compression performance of the amorphous alloy decreases sharply.
[0027] Figure 7The SEM images of the side of the sample in the cast state, after isothermal annealing at 741K, 746K, 751K and 756K are shown. It can be seen from the figure that with the increase of isothermal annealing temperature, the number of shear bands on the side of the amorphous alloy sample shows a trend of first increasing and then decreasing. A large number of interwoven shear bands are distributed on the side of the samples isothermal annealed at 741K and 746K. There are only a few main shear bands on the side of the sample isothermal annealed at 751K, and the interaction between the shear bands is weak. There is only one obvious crack on the side of the sample isothermal annealed at 756K.
[0028] The room temperature compression fracture of amorphous alloys is mainly achieved through the initiation and expansion of highly localized shear bands. The amorphous deformation process will first lead to the generation and aggregation of free volume, and then trigger the initiation of local softening-induced shear bands. There is an adiabatic heating effect in its expansion process, which will cause remelting in local areas of the amorphous matrix. Therefore, molten droplets that solidify after remelting are found on the fracture surface.
[0029] After different isothermal annealing treatments, the initiation and expansion of shear bands during deformation also change due to the change in the structure of the amorphous matrix. After isothermal annealing at lower temperatures (741K and 746K), the amorphous matrix still maintains most of the amorphous structure, and the initiation of shear bands is still triggered by the generation and aggregation of free volume during deformation. However, during the expansion process, due to the "pinning" effect of the dispersed Cu10Zr7 nano-precipitates, the shear band expansion direction is deflected and the tip is passivated, inducing the proliferation of shear bands and avoiding the high localization of shear bands near the fracture. The shear bands diffuse to the side fracture area over a large area, effectively hindering the rapid expansion of the shear bands and improving the strength and plasticity of the alloy.
[0030] As the isothermal annealing temperature continues to increase, a large amount of brittle phase (AlCu2Zr phase) precipitates in the amorphous matrix, and the size of various crystals further increases, resulting in stress concentration at the interface between the amorphous matrix and the crystal phase during the deformation process, forming structural defects such as micropores, which aggregate, grow and expand, and eventually form microcracks, causing brittle fracture of the alloy.
[0031] Therefore, the Cu45Zr45Ag7Al3 amorphous alloy precipitates different crystallized phases with the increase of isothermal annealing temperature. After isothermal annealing at 741K and 746K, dispersed nanoscale Cu10Zr7 phases are precipitated, but the size and density are different; after isothermal annealing at 751K, Cu10Zr7 and cellular AlCu2Zr are precipitated; after isothermal annealing at 756K, crystallization is more obvious, mainly AlCu2Zr, Cu10Zr7, and Cu8Zr3 phases; With the increase of annealing temperature, the fracture strength and plastic strain of Cu45Zr45Ag7Al3 amorphous alloy first increase and then decrease, among which the fracture strength reaches the maximum value (MPa) at 741K, and the plastic strain reaches the maximum value (0.82%) at 746K; The nanoscale Cu10Zr7 phase precipitated in the alloy after isothermal annealing at 741K and 746K plays a "pinning" role, effectively hindering the expansion of the shear band and improving the plasticity of the alloy. The precipitation of the AlCu2Zr brittle phase after isothermal annealing at 751K and 756K will lead to the deterioration of the alloy's plasticity.
[0032] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.
Claims
1. An isothermal annealing process for an amorphous alloy, characterized in that: The following steps are involved: S1, take 45-50 parts of high-purity sponge zirconium, 45-50 parts of copper, 7-10 parts of pure aluminum and 3-5 parts of silver as raw materials, put them into a mixing device and mix them evenly; S2, using arc melting vacuum suction casting method, the mixed material in S1 is used to prepare Φ4mm×80mm alloy round rods; S3, placing the alloy round bar in step S2 into a trolley-type heat treatment furnace, and gradually heating the alloy round bar to between 980°C and 1000°C; S4. Open the furnace door and let the temperature in the heat treatment furnace drop naturally to 750 degrees, then close the furnace door and keep it warm for 5h-7h; S5, after step S4, controlling the temperature inside the heat treatment furnace to gradually drop to 450°C; S6. After the processing in step S5, the workpiece is taken out from the heat treatment furnace and naturally air-cooled.
2. The isothermal annealing process of an amorphous alloy according to claim 1, characterized in that: Take 45 parts of the high-purity sponge zirconium, 45 parts of the copper, 7 parts of the pure aluminum, and 3 parts of the silver, and use ultrasonic vibration to clean the accurately weighed metal elements.
3. The isothermal annealing process of an amorphous alloy according to claim 1, characterized in that: The purity of the high-purity sponge zirconium is 99.9%, the purity of the copper is 99.8%, the purity of the pure aluminum is 99.9%, and the purity of the silver is 99.99%.
4. The isothermal annealing process of an amorphous alloy according to claim 1, characterized in that: In the step S2, the heating rate of the alloy round rod is less than 200° C. / hour.
5. The isothermal annealing process of an amorphous alloy according to claim 1, characterized in that: In step S5, the temperature inside the heat treatment furnace decreases at a rate of 50° C. / hour.